Respuesta :
Answer: The correct options are (1) (5,10), (2) (3,-3), (3) x = -1, (4) [tex]y=(x+2)^2+3[/tex], (5) 21s and (6) 0, -1, and 5.
Explanation:
Te standard form of the parabola is,
[tex]f(x)=a(x-h)^2+k[/tex] .....(1)
Where, (h,k) is the vertex of the parabola.
(1)
The given equation is,
[tex]f(x)=(x-5)^2+10[/tex]
Comparing this equation with equation (1),we get,
[tex]h=5[/tex] and [tex]k=10[/tex]
Therefore, the vertex of the graph is (5,10) and the fourth option is correct.
(2)
The given equation is,
[tex]f(x)=3x^2-18x+24[/tex]
[tex]f(x)=3(x^2-6x)+24[/tex]
To make perfect square add [tex](\frac{b}{2a})^2[/tex], i.e., [tex]9[/tex]. Since there is factor 3 outside the parentheses, so subtract three times of 9.
[tex]f(x)=3(x^2-6x+9)+24-3\times 9[/tex]
[tex]f(x)=3(x-3)^2-3[/tex]
Comparing this equation with equation (1),we get,
[tex]h=3[/tex] and [tex]k=-3[/tex]
Therefore, the vertex of the graph is (3,-3) and the fourth option is correct.
(3)
The given equation is
[tex]f(x)=4x^2+8x+7[/tex]
[tex]f(x)=4(x^2+2x)+7[/tex]
To make perfect square add [tex](\frac{b}{2a})^2[/tex], i.e., [tex]1[/tex]. Since there is factor 4 outside the parentheses, so subtract three times of 1.
[tex]f(x)=4(x^2+2x+1)+7-4[/tex]
[tex]f(x)=4(x+1)^2+3[/tex]
Comparing this equation with equation (1),we get,
[tex]h=-1[/tex] and [tex]k=3[/tex]
The vertex of the equation is (-1,3) so the axis is x=-1 and the correct option is 2.
(4)
The given equation is,
[tex]y=x^2+4x+7[/tex]
To make perfect square add [tex](\frac{b}{2a})^2[/tex], i.e., [tex]2^2[/tex].
[tex]f(x)=x^2+4x+4+7-4[/tex]
[tex]f(x)=x^2+4x+4+7-4[/tex]
[tex]f(x)=(x+2)^2+3[/tex]
Therefore, the correct option is 4.
(5)
The given equation is,
[tex]h=-16t^2+672t[/tex]
It can be written as,
[tex]h=-16(t^2-42t)[/tex]
It is a downward parabola. so the maximum height of the function is on its vertex.
The x coordinate of the vertex is,
[tex]x=\frac{b}{2a}[/tex]
[tex]x=\frac{42}{2}[/tex]
[tex]x=21[/tex]
Therefore, after 21 seconds the projectile reach its maximum height and the correct option is first.
(6)
The given equation is,
[tex]f(x)=3x^3-12x^2-15x[/tex]
[tex]f(x)=3x(x^2-4x-5)[/tex]
Use factoring method to find the factors of the equation.
[tex]f(x)=3x(x^2-5x+x-5)[/tex]
[tex]f(x)=3x(x(x-5)+1(x-5))[/tex]
[tex]f(x)=3x(x-5)(x+1)[/tex]
Equate each factor equal to 0.
[tex]x=0,-1,5[/tex]
Therefore, the zeros of the given equation is 0, -1, 5 and the correct option is 2.